Geomorphological hazards of Europe - Embleton, Clifford; Embleton-Hamann, Christine (Developments in earth surface processes, 1997)
The Geomorphological Hazards of Europe contains an excellent balance of authoritative statements on the range and causes of natural hazards in Europe. Written in a clear and unpretentious style, it removes myths and concentrates on the basic facts. The book looks at the known distributions, processes and the underlying principles and focuses on the need for a true understanding of the scientific details so that a real contribution to hazard management can be made. A comprehensive treatment of scientific and management issues of hazards in Europe caused by natural or sometimes human induced earth surface processes are covered including floods, landslides, avalanches, glacier-, coastal-, karstic-, and volcanic hazards, soil erosion and subsidence. Leading researchers in the field of natural hazards and their mitigation have contributed to this nation by nation account covering 20 European countries. The individual chapters deal with the distribution of natural hazards within specific countries (quite often the first synthesis of the information available) and & bull; provide a review of current research in the field & bull; discuss the economic, engineering and policy responses in national hazard management & bull; are complemented by an extensive bibliography. The volume is well illustrated with 207 figures of which 66 are photos and has an extensive general index and a complete index of place names. It is a major European contribution to the International Decade for Natural Disasters Reduction. The book will appeal to practitioners, managers, academicians, researchers, as well as graduate students in geomorphology, natural hazards research and environmental management.